Methodological instructions for independent works in the "Computer electronics" academic discipline - Skorodielov, Volodymyr Vasyliovych; Podorozhniak, Andrii Oleksiiovych (National technical university "Kharkiv polytechnic institute", 2024)
Computer electronics is one of the fundamental disciplines in the field of Computer Engineering. This discipline provides the theoretical and engineering training necessary to perform research and practical work on the research, development and operation of computer hardware, embedded microprocessor and microcontroller systems, computer systems and networks for various purposes (information, medical and industrial). As a result of studying the academic discipline, students should know: classification and purpose of the main elements and basic nodes of analog devices, the basics of their operation, characteristics, parameters and equivalent circuits; basics of analysis and calculation of electronic circuits; basic principles of construction and operation of various types of analog devices, such as amplifiers, generators, power sources, etc. Also, students should be able to use various electronic devices in electronic circuits, evaluate the parameters of electronic devices depending on the features of their use; analyze and develop circuits of electronic devices of functional units of computers based on analog microcircuits; measure parameters, find malfunctions, debug and test analog devices and nodes, as well as operate them; use technical and reference literature, as well as standards in their development and operation; to use electronic circuit simulation programs when developing analog devices. It is obvious that such a large amount of knowledge and skills cannot be mastered qualitatively without regular and rather intense independent work of students both during classroom classes and during independent work at home. Independent work develops the skills of continuous self-improvement and the ability to self-educate, activates search and research activities and provides an opportunity to acquire knowledge that is necessary for conducting practical and scientific activities.
Keywords: methodological instructions; electronic circuits; microcontroller systems; networks; computer hardware; linear circuits; power sources